(untitled) (Iranian Journal of Kidney Diseases, 2022)
Nephrolithiasis is a common disease entity around the world, with an increasing prevalence and incidence. There is no consolidated information available on the cause of kidney stones in Iranian patients. As a result, we decided to review the etiology of kidney stones in Iran. PubMed, Scopus, Web of Science, Google scholar, and Scientific Information Database (SID) were searched with the following keywords “Nephrolithiasis”, “Renal stone”, “Kidney stone”, “Urolithiasis”, “Etiology”, “Metabolic abnormalities”, and “Iran”. There was no time period limit for selection of the papers. The inclusion criteria included any paper on evaluation of urine biochemistry regarding stone formation in Iranian adult patients (with or without children) with nephrolithiasis. We found 217 articles, of which 9 were eventually included. In conclusion, 1896 patients with nephrolithiasis from 6 provinces and 7 cities of Iran with different climates from 2000 to 2019 were evaluated collectively. The results showed that in contrast to western countries, hypercalciuria was not the most common biochemical disorder of patients with nephrolithiasis (18.2% vs. 30 to 60%). Low urine volume (49.6%) and hypocitraturia (27%) were the most frequent urine abnormalities in our country. DOI: 10.52547/ijkd.7055